2023
DOI: 10.1029/2023jd038843
|View full text |Cite
|
Sign up to set email alerts
|

Triple‐Dip La Niñas in 1998–2001 and 2020–2023: Impact of Mean State Changes

Xiaofan Li,
Zeng‐Zhen Hu,
Michael J. McPhaden
et al.

Abstract: This study compares the evolution of atmospheric and oceanic anomalies as well as predictions for the two most recent triple‐dip La Niña events in 1998–2001 and 2020–2023. Subsurface cooling in the equatorial Pacific was stronger and more persistent during 1998–2001. In contrast, surface easterly winds were stronger during 2020–2023 as was the east‐west sea surface temperature (SST) contrast along the equator. We argue that in the absence of appreciable equatorial Pacific heat discharge, persistent and strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…Extreme El Niño events strongly enhance the overall El Niño/Southern Oscillation (ENSO) asymmetry 7 , 8 , with their large amplitude in the eastern Pacific indeed intensifying and shifting the El Niño signals eastward relative to those of La Niña 9 . The ENSO phase transition also displays asymmetry 10 , often transitioning from extreme El Niño to La Niña, while La Niña events can persist for multiple years, as exemplified by triple-dip La Niña 11 from mid-2020 to early 2023. ENSO amplitude, spatial pattern and duration asymmetries are closely tied to its diversity 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Extreme El Niño events strongly enhance the overall El Niño/Southern Oscillation (ENSO) asymmetry 7 , 8 , with their large amplitude in the eastern Pacific indeed intensifying and shifting the El Niño signals eastward relative to those of La Niña 9 . The ENSO phase transition also displays asymmetry 10 , often transitioning from extreme El Niño to La Niña, while La Niña events can persist for multiple years, as exemplified by triple-dip La Niña 11 from mid-2020 to early 2023. ENSO amplitude, spatial pattern and duration asymmetries are closely tied to its diversity 12 .…”
Section: Introductionmentioning
confidence: 99%
“…For the coastal El Niño in 2017, SSTA warming in the Niño1+2 region began in late 2016 and was larger than 0.5°C during January-April 2017 with a peak value of 1.8°C in March 2017 (the black line in Figure 2a). The Niño3.4 index (the shading in Figure 2a) was negative in July-December 2016, consistent with the La Niña conditions, Similarly, SSTA warmed up quickly in the Niño1+2 region beginning in late 2022 after the triple-dip La Niña during 2020-2023 (Hasan et al, 2022;Jiang et al, 2023;Li et al, 2022Li et al, , 2023bZhang et al, 2022) (the black line in Figure 2b). The peak of the coastal El Niño appeared in August 2023 with the value of 3.30°C for the Niño1+2 index, exceeding 3 standard deviations (Figure S1a in Supporting Information S1).…”
Section: Temporal Evolution Of the Coastal El Niños In 2017 And 2023mentioning
confidence: 53%
“…Similarly, SSTA warmed up quickly in the Niño1+2 region beginning in late 2022 after the triple‐dip La Niña during 2020–2023 (Hasan et al., 2022; Jiang et al., 2023; Li et al., 2022, 2023b; Zhang et al., 2022) (the black line in Figure 2b). The peak of the coastal El Niño appeared in August 2023 with the value of 3.30°C for the Niño1+2 index, exceeding 3 standard deviations (Figure S1a in Supporting Information ).…”
Section: Resultsmentioning
confidence: 94%
“…(2020) suggested that an enhanced zonal contrast along the tropical Pacific with appreciable warming in the west and slight cooling in the east may affect the ENSO evolution and prediction. Such impact was evident in the triple‐dip La Niña during 2020–2023 (Li, Hu, et al., 2023).…”
Section: Multi‐time Scale Variations and A Relative Atlantic Niño Indexmentioning
confidence: 99%